Population growth in cities in the south and southwest of Minas Gerais to determine landfill area (Research, Society and Development, 2021)
The knowledge of the minimum area of ​​a landfill is one of the initial steps for its implementation, the use of estimates of population and economic growth has been shown to be very effective in determining the minimum area of ​​the landfill. This work aimed to determine the minimum landfill area using the population growth estimate, as well as the use of the country's current economic development. To compose this study, the municipalities were divided into micro-regions established through proximity and 2 or 3 municipalities from each of the micro-regions were chosen at random. The final population of each municipality was calculated at the end of the landfill's useful life and the population after 25 years was estimated to know the volume of garbage in 2045. The results found in this work confirm the theory that the larger, more developed and more the population is rich, more solid waste is generated, as the diversity found in landfill sizes was directly related to population size and development. The smallest landfill area estimated at 10,600 m² was in Fama and the largest 688,560 m² in the city of Poços de Caldas.